2010
DOI: 10.1007/s11999-009-1178-y
|View full text |Cite
|
Sign up to set email alerts
|

Cost Analysis of Outpatient Anterior Cruciate Ligament Reconstruction: Autograft versus Allograft

Abstract: BackgroundPrior studies suggest the cost of allograft anterior cruciate ligament (ACL) reconstruction is less than that for autograft reconstruction. Charges in these studies were influenced by patients requiring inpatient hospitalization.Question/purposeWe therefore determined if allograft ACL reconstruction would still be less costly if all procedures were performed in a completely outpatient setting.MethodsWe retrospectively reviewed 155 patients who underwent ACL reconstruction in an ambulatory surgery cen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
62
0
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(65 citation statements)
references
References 14 publications
0
62
0
3
Order By: Relevance
“…Nagda et al [34], however, found that the total treatment costs for autograft patients were lower owing to the high cost of the allograft.…”
Section: Discussionmentioning
confidence: 99%
“…Nagda et al [34], however, found that the total treatment costs for autograft patients were lower owing to the high cost of the allograft.…”
Section: Discussionmentioning
confidence: 99%
“…Further, it has been suggested that mismatch in age, activity and body weight between donor and recipient may be crucial factors in the failure of allografts for ACL reconstruction [304]. In addition, the use of allografts is further limited by their higher overall surgical costs; approximately US$ 1,000 extra per clinical case [305,306]. For these reasons, the use of xenografts took off, with numerous products currently available [307,308].…”
Section: Tissue Grafts -The Top-down Approach For Tendon Repairmentioning
confidence: 99%
“…Despite the abundance of operative techniques, there is still a need for less invasive surgical approaches that preserve soft tissue integrity and are more reproducible and less technically challenging than those currently available. [30][31][32][33][34] The purpose of this study was to systematically evaluate surgical reconstruction techniques of the MCL and posteromedial corner of the knee. We hypothesized that anatomic medial knee reconstruction would result in superior measures of valgus laxity and functional patient-reported outcomes when compared with other nonanatomic surgical techniques.…”
mentioning
confidence: 99%